2014
DOI: 10.1097/iae.0000000000000165
|View full text |Cite
|
Sign up to set email alerts
|

Hyperreflective Pyramidal Structures on Optical Coherence Tomography in Geographic Atrophy Areas

Abstract: We describe a multimodal imaging of distinctive lesions that presented as hyperreflective pyramidal structures on SD-OCT. We suggest the name "ghost drusen" because these HPS appear in GA areas, and because of their pyramidal or dome-shaped aspect on SD-OCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 41 publications
(48 reference statements)
1
30
0
Order By: Relevance
“…Fleckenstein et al 15 using SD-OCT described in GA areas elevations with crownlike appearance with presumed debris beneath. Recently, Bonnet et al 20 reported on hyperreflective structures in GA areas, which the authors suggested to name as "ghost drusen." As for wedge-shaped subretinal hyporeflective lesions, also these structures, which were smaller and crownlike/pyramidal rather than wedge-shaped, often correlated with an increased FAF signal within the atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Fleckenstein et al 15 using SD-OCT described in GA areas elevations with crownlike appearance with presumed debris beneath. Recently, Bonnet et al 20 reported on hyperreflective structures in GA areas, which the authors suggested to name as "ghost drusen." As for wedge-shaped subretinal hyporeflective lesions, also these structures, which were smaller and crownlike/pyramidal rather than wedge-shaped, often correlated with an increased FAF signal within the atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…The distinctive feature as seen by SD-OCT imaging was a laminar intense hyperreflectivity at the level of Bruch's membrane or a pyramidal structure at the level of the outer retina (''ghost drusen''). 22,41,42 One of the two eyes with refractile deposits presented RDR, while the presence of refractile deposits and the local atrophy development appeared not to be spatially associated with RDR presence. Further, progressive disruption of outer retinal bands by SD-OCT was noted.…”
Section: Type 2c: Association With Refractile Depositsmentioning
confidence: 99%
“…Shortly after, in the same year, Bonnet et al described their own findings in patients with GA (Bonnet et al, 2014). These authors preferred to introduce the term "hyperreflective pyramidal structures" (HPS) to describe the same OCT feature that Ooto and colleagues had called outer retinal corrugations (Bonnet 2014).…”
mentioning
confidence: 99%
“…Using short wavelength autofluorescence, HPS were most commonly hypoautofluorescent, in 57 of 96 cases (59%). Multicolor reflectance imaging identifies these structures as having a "peculiar green reflectivity" (Bonnet et al, 2014). Imaging with SD-OCT, HPS present a heterogeneous hyper-reflective internal boundary with a hyporeflective core.…”
mentioning
confidence: 99%
See 1 more Smart Citation